Comment on Assessing Prior Distributions for Applying Bayesian Statistics in Auditing: A Reply. - Corless, John C. (The Accounting Review, 1975)
Abstract Presents a reply to Bart Ward's commentary on the assessment of prior distributions for applying Bayesian statistics in auditing. Assumption regarding the problem of obtaining prior distributions of good quality; Fallacy of Ward's reasoning.